Tackling antimicrobial stewardship through synergy and antimicrobial peptides. Issue 5 (19th April 2022) - Greve, Jenna M.; Cowan, James A.
Abstract : This review summarizes the most common mechanisms of antibiotic action and resistance, emphasizing antimicrobial peptides and focusing on emerging strategies and the role of antimicrobial synergy. Abstract : The unrestricted use of antibiotics has led to rapid development of antibiotic resistance (AR) and renewed calls to address this serious problem. This review summarizes the most common mechanisms of antibiotic action, and in turn antibiotic resistance, as well as pathways to mitigate the harm. Focus is then turned to emerging antibiotic strategies, including antimicrobial peptides (AMPs), with a discussion of their modes of action, biochemical features, and potential challenges for their use as antibiotics. The role of synergy in antimicrobials is also examined, with a focus on the synergy of AMPs and other emerging interactions with synergistic potential.